THE EFFECT OF USING CHAT GPT ON THE COMPETENCE OF ACCOUNTING STUDENTS - Mediaty Mediaty; Abd. Hamid Habbe; Anne Kurry Anggreani; Eka Amelia; Andi Aliyyah Ramadhani Sam; Nalendra Bhayu Permana (Politeknik Negeri Ambon, 2025)
Introduction: This study aims to analyze the effect of using ChatGPT on the competence of accounting students at Hasanuddin University. In the era of rapid information technology revolution, ChatGPT as one of the artificial intelligence (AI) technologies has become a significant tool in the world of education, including accounting education. Methods: This study uses a quantitative approach with an explanatory method to test the hypothesis about the relationship between the use of ChatGPT and student competence. Data were collected through distributing online questionnaires to Master of Accounting students and analyzed using the SmartPLS application. Results: The results showed that the use of ChatGPT has a positive and significant influence on improving student competence, especially in the aspects of analysis and understanding of accounting concepts. The findings support the importance of integrating AI technology in learning to improve the effectiveness of accounting education, although it also highlights the need for wise use to prevent potential negative impacts, such as reduced critical thinking skills. This research provides an empirical contribution to the development of learning strategies that integrate technology with academic ethical values. Keywords: ChatGPT, Student Competency, Accounting